How is honey made? - Hansen, Grace (Minneapolis, Minn. : Abdo Kids Jumbo, an imprint of Abdo Kids, 2019)
"This title will take readers through the process of making honey, beginning with honey bees and how they create honeycomb in their hives. Then it will show readers how honeycomb is gathered without harming honey bees, and how honey is extracted from it" --
Sweet honeybees -- The beekeeper -- The honey factory -- More facts.
Includes index.
Ages 4-9
Keywords: Honey -- Juvenile literature; Bee products industry -- Juvenile literature; Honeybee -- Juvenile literature; Bee culture -- Juvenile literature; Bee culture; Bee products industry; Honey; Honeybee; Manufacturing processes; Juvenile works